Tengku Mahkota of Pahang launched Kuala Pahang Mahkota Empower ECER - UMP, PNC
His Royal Highness Tengku Mahkota of Pahang Tengku Abdullah Al-Haj Ibni Sultan Haji Ahmad Shah Al-Musta’in Billah officially launched Kuala Pahang Mahkota Empower ECER - a human resource development programme tailored especially for the community in Kuala Pahang, Pekan.